2017
DOI: 10.1002/slct.201700009
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy Metabolomics Applied to Crack Cocaine Users and Patients with Schizophrenia: Similar Behavior but Different Molecular Causes

Abstract: Crack-cocaine abuse and dependence is a severe public health problem. Sometimes, the crack-cocaine smokers show behavioral changes and symptoms very similar to those observed for severe mental disorders, like schizophrenia. Although crackcocaine use can easily be detected in smokers by urine or blood tests, after some time, cocaine biomarkers become untraceable. In addition, schizophrenia diagnosis is limited to clinical interviews, while precise clinical tests for this mental disorder remain unknown. Employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recently, we have demonstrated that by using 1 H NMR-based metabolomics it was possible to separate healthy control (HC) individuals from schizophrenia or from bipolar patients . Also, we have demonstrated that it is possible to employ the same technique to discriminate crack users and schizophrenia patients who may share similar symptoms . In the present research, we performed 1 H NMR-based metabonomic analysis of crack users’ serum samples aiming to understand the metabolic changes related to the drug disorder and identify biomarkers that might be correlated with brain dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, we have demonstrated that by using 1 H NMR-based metabolomics it was possible to separate healthy control (HC) individuals from schizophrenia or from bipolar patients . Also, we have demonstrated that it is possible to employ the same technique to discriminate crack users and schizophrenia patients who may share similar symptoms . In the present research, we performed 1 H NMR-based metabonomic analysis of crack users’ serum samples aiming to understand the metabolic changes related to the drug disorder and identify biomarkers that might be correlated with brain dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…Desirable biomarker candidates should have features including their correlation with functional outcomes and practical, inexpensive, reproductive, and non-invasive methods of their determination and monitoring [13,14]. Currently, proteomics, genomics, and metabolomics are important platforms for measuring potential biomarkers in psychiatric diseases [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%